ISLAMIC RELIGIOUS EDUCATION CURRICULUM DESIGN BASED ON COMPETENCE IN IMPROVING SKILLS STUDENT SOCIAL - Yusuf, M. Isa (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study examines the design and implementation of a competency-based Islamic Religious Education (PAI) curriculum aimed at enhancing students' social skills, addressing the gap between theoretical frameworks and practical application. Method: Utilizing a library research approach, this study analyzes data from scientific journal articles and published research reports in the field of education. The investigation focuses on curriculum structure, expected competencies, and its impact on students' social interactions. Results: The findings indicate that a competency-based PAI curriculum integrates religious education with social skill development, emphasizing communication, cooperation, and empathy. The curriculum employs experience-based learning, character building, and social-oriented assessments. Key competencies include conflict resolution, social independence, and the application of religious values in daily interactions. The implementation of this curriculum has demonstrated a positive impact on students' social interactions, fostering improved cooperation, tolerance, and conflict management, leading to a more inclusive and harmonious school environment. Novelty: This study highlights the integration of religious education with structured social skill development, providing a comprehensive approach to fostering social competence among students. The findings contribute to the discourse on competency-based curriculum models, emphasizing the role of religious values in shaping constructive social behavior.